Application of failure mode and effect analysis in managing catheter-related blood stream infection in intensive care unit. Issue 51 (December 2017) - Li, Xixi; He, Mei; Wang, Haiyan
Abstract : Abstract: In this study, failure mode and effect analysis (FMEA), a proactive tool, was applied to reduce errors associated with the process which begins with assessment of patient and ends with treatment of complications. The aim of this study is to assess whether FMEA implementation will significantly reduce the incidence of catheter-related bloodstream infections (CRBSIs) in intensive care unit. The FMEA team was constructed. A team of 15 medical staff from different departments were recruited and trained. Their main responsibility was to analyze and score all possible processes of central venous catheterization failures. Failure modes with risk priority number (RPN) ≥100 (top 10 RPN scores) were deemed as high-priority-risks, meaning that they needed immediate corrective action. After modifications were put, the resulting RPN was compared with the previous one. A centralized nursing care system was designed. A total of 25 failure modes were identified. High-priority risks were "Unqualified medical device sterilization" (RPN, 337), "leukopenia, very low immunity" (RPN, 222), and "Poor hand hygiene Basic diseases" (RPN, 160). The corrective measures that we took allowed a decrease in the RPNs, especially for the high-priority risks. The maximum reduction was approximately 80%, as observed for the failure mode "Not creating the maximal barrier for patient." The averaged incidence of CRBSIs was reduced from 5.19% to 1.45%, with 3 months of 0 infection rate. The FMEA can effectively reduce incidence of CRBSIs, improve the security of central venous catheterization technology, decrease overall medical expenses, and improve nursing quality.